Rapamycin alleviates cognitive impairment in murine vascular dementia: The enhancement of mitophagy by PI3K/AKT/mTOR axis. (April 2021) - Zheng, Guimin; Wang, Lei; Li, Xiuqin; Niu, Xiaoli; Xu, Guodong; Lv, Peiyuan
Highlights: Rapamycin improved the cognitive impairment after vascular dementia (VaD). Rapamycin alleviated neuronal injury and mitochondrial dysfunction in VaD rats. Rapamyciny inhibited neuronal apoptosis and enhanced mitophagy in VaD rats. Abstract: There are no approved symptomatic treatments for vascular dementia (VaD). Rapamycin (RAPA) improves cognitive deficits in Alzheimer's disease rats. To explore whether RAPA improves cognitive impairment after VaD and its possible molecular mechanisms. Thirty Sprague Dawley rats were randomly divided into three groups: sham (received sham-operation), VaD model (received permanent ligation of bilateral carotid arteries) and RAPA (7.5 mg/kg) treatment. Cognitive function was evaluated by Morris water maze test. Neuronal apoptosis was evaluated by TUNEL staining. Mitophagy was assessed by mitochondrial DNA (mtDNA), ATP level, transmission electron microscope and mitophagy-associated proteins. Proteins were quantified by Western blot and immunofluorescence. BV2 cells were exposed to RAPA or/and MHY1485 (mTOR activator) to verify in vivo results. Compared to VaD rats, the escape latency of RAPA-treated rats was significantly decreased, and time spent in target quadrant was longer. Pathologic changes, mitochondrial dysfunction, increase of neuronal apoptosis and related proteins in VaD rats were remarkably alleviated by RAPA. After RAPA treatment, an increase in number of autophagosomes was observed, along with up-regulation of mitophagy-related proteins. Overexpression of PI3K, AKT and mTOR were suppressed by RAPA treatment. In vitro experiments confirmed effects of RAPA, and demonstrated that MHY1485 addition reversed the RAPA-caused apoptosis inhibition and mitophagy enhancement. Overall, RAPA improved the cognitive impairment of VaD rats, alleviated neuronal injury and mitochondrial dysfunction. We proposed a potential mechanism that RAPA may play improving role by inhibiting neuronal apoptosis and enhancing mitophagy through PI3K/AKT/mTOR pathway. Findings provided an exciting possibility for novel treatment strategy of VaD.